PENGARUH PEMBERDAYAAN SUMBER DAYA MANUSIA DAN KOMPENSASI TERHADAP KINERJA PEGAWAI BAGIAN HUMAS KANWIL KEMENTERIAN AGAMA PROPINSI DKI JAKARTA - Rohaeni, Heni (Universitas Islam Negeri Raden Intan Lampung, 2016)
Abstract-Performance problems are not limited to how much the organization is able to empower human resources as members of the organization to achieve the desired work but furthermore is how successful is the organization can encourage motivation and satisfaction of employees to work as much as possible so they can achieve the expected performance. One way to encourage motivation and employee satisfaction is the reward or remuneration in this case is compensated either directly or indirectly adequate, so that employees feel that the organization has noticed at once appreciate what they have done for the sake of the organization, with thus, the employee's performance will be achieved, but on the contrary, if the organization failed to give attention in this case the compensation of employees it is not impossible employees are not motivated to work so consequently performance is not achieved according to expectations of the organization and as a result of dissatisfaction of employees that compensation will make the performance more decreasses. Method research conducted in this study is a survey research design with quantitative research methods. That quantitative research is research conducted to determine the value of self, either one or more variables (independent) without making comparisons or connections between the variables of the other variables, whereas associative research is research that aims to determine the relationship between two or more variables, with emphasis see a causal relationship is a causal relationship. The results of this study variable data Empowerment of Human Resources showed that the lowest score of 67 and the highest score was 93. Thus, obtaining the highest and lowest scores, the range of scores (range) was 26 (93-67). Compensation variable data indicate that the lowest score was 51 and the highest score was 71. Thus, obtaining the highest and lowest scores, the range of scores (range) was 20 (71-51). for employee performance variable data shows that the lowest score was 55 and the highest score was 74. Thus, obtaining the highest and lowest scores, the range of scores (range) was 19 (74-55).